(untitled) (Argumentum, 2012)
This paper is about the targeting of the UK health service by private international health care corporations who want to get their hands on the £200b annual budget and the collusion in that project by successive governments, including the present administration led by David Cameron which is the most ideologically driven government that we have had in the UK in my lifetime – more radical in their dismantling of our welfare state than Margaret Thatcher in the 1980s but building upon her legacy. It is a tale about neo-liberalism, about the power of global business interests, about privatisation, about reducing the role of the state, and about a weak democracy. And so it is a cautionary tale about progress – even when affordable universal health care has been secured, it is not immune from attack and from being reversed.